Embracing both sides of the financial coin for a sustainable future and inclusive growth, by Zunaidah Sulong, Hartini Ab. Ghani, and Salman Lambak (eds.). 2022. Penerbit UniSZA, Universiti Sultan Zainal Abidin: Malaysia. 191 pages. ISBN: 978967-2750-32-1. - Ariffin, Muhammad Irwan (Penerbit Universiti Islam Selangor (UIS), 2024)
This book aims to provide conceptual clarification on the theoretical and practical issues surrounding conventional and Islamic finance, Islamic philanthropy, financial institutions, and big data analytics. There are nine chapters in the book that are divided into two parts based on their common themes. The first part is on Islamic finance and financial institutions with six chapters, while the remaining three chapters are grouped under part 2 on finance, banking and big data analytics.